Spaceborne High-resolution Stepped-frequency SAR Imaging Technology - LONG Teng; DING Zegang; XIAO Feng; WANG Yan; LI Zhe (Leida xuebao, 2019)
Spaceborne Synthetic Aperture Radar (SAR) is a type of microwave imaging radar with 2D high resolution. This technological device achieves range high resolution by transmitting wideband signals and azimuth high resolution through the synthetic aperture approach. With the increasing demand for high-resolution imaging, the resolution of spaceborne SAR has moved toward the decimeter level. On the one hand, limited by the present hardware technology, achieving wideband signal transmission through stepped-frequency technology is necessary. In this case, we need to study high-precision bandwidth synthesis technology. The influence of slant range error and amplitude and phase error between sub-bands should be considered. On the other hand, due to limited beamwidth, the system needs to work in sliding spot mode to achieve a long synthetic aperture. In this case, we need to study the problem of imaging parameter variance caused by curved orbit, “Stop–go” error, and the influence of ionospheric and tropospheric transmission errors on imaging. To solve these problems, this paper introduces the principle of stepped-frequency signal design and bandwidth synthesis technology in detail. A time-domain algorithm and non-ideal factor compensation method are proposed for spaceborne high-resolution stepped-frequency SAR imaging. Finally, simulation verification and performance analysis of the imaging algorithm are conducted.